The Transferability of Sport Coaching Research: A Critical Commentary. Issue 4 (2nd October 2018) - Lyle, John
ABSTRACT: The utility and applicability of research in sport coaching is widely reported to be problematic. This article offers a critical commentary on the factors impacting the potential transferability of research findings into coaches' practice and into coach education, arguing that a more nuanced appreciation of these factors is necessary. The issue is conceptualized as one of knowledge transfer, and the article examines the roles of the researcher and the practitioner in facilitating research-informed practice. Single-focus disciplinary research, an absence of application research and the paucity of studies on coaching interventions are identified as limiting factors. A more realistic appreciation of the particularity of role, domain, and context is required, along with a recognition of their influence on coaches' perceptions of the relevance of research findings. It is suggested that the inertia of academic publishing practice may continue to constrain more pragmatic and interdisciplinary research in this field.